Learning Management Based on Active Deep Learner Experience (ADLX) in Developing Teacher Innovation and Competence (Case Study at SMPIT Al Uswah Surabaya) - Ismiatiningsih Ismiatiningsih*; Erny Roesminingsih; Karwanto Karwanto (Universitas Syiah Kuala, 2023)
SMPIT Al Uswah is one of the SMPITs under the auspices of the Integrated Islamic School Network which implements a learning system that prioritizes memorizing the Koran and also leadership, according to the school's motto, namely